Late diagnosis of pseudohypoparathyroidism in adulthood. Case series (2018)
ABSTRACT: Introduction: Pseudohypoparathyroidism (PHP) is a rare hereditary disease, characterized by hypocalcemia/hyperphosphatemia secondary to peripheral resistance to parathyroid hormone (PTH). PHP diagnosis is usually precluded since hypocalcemia is considered as the primary diagnosis, thus delaying further diagnostic studies and preventing an adequate management of this clinical condition. Materials and methods: Retrospective review of the databases of the Endocrinology departments of two tertiary care centers of Medellin, Colombia from January 2012 to December 2016. Patients diagnosed with PHP based on clinical presentation and confirmatory laboratory values were included. Results: Four patients met the inclusion criteria. All PHP cases were diagnosed in adulthood despite strong early clinical and laboratory evidence of the disease. Three patients were diagnosed with Fahr’s syndrome and two with Albright’s hereditary osteodystrophy. The mean values obtained were PTH of 376.8 pg/mL, calcium of 6.17 mg/dL and phosphorus of 6.55 mg/dL. Conclusions: PHP is a rare disorder. This paper describes four PHP cases diagnosed during adulthood. Emphasis should be placed on the judicious approach to the patient with hypocalcemia and hyperphosphatemia with increased PTH and normal renal function, since these symptoms strongly suggest a diagnosis of PHP.